Human capital and intergenerational occupational mobility: Some evidence for Spain - Caparrós-Ruiz, Antonio (My University, 2015)
Intergenerational occupational mobility is a topic that has attracted considerable interest in the economic literature for developed countries. Particularly, one of the central issues in political debate is the role of education on the intergenerational social mobility. The modern capitalist economies are characterised by continual technological changes which lead to the need of a highly skilled workforce. In this potentially meritocratic society, the equality of opportunities, the efficient allocation of talent and the education can be instruments that encourage the social mobility and decrease the effect of the parent’s economic status on the career of their children. However, nowadays, there are still some factors that can hinder the achievement of a more equal society. Some of these elements are discrimination, failures of the education system or capital market imperfections. This paper takes into account these facts and sheds empirical evidence for Spain about the relationships between social origin, educational attainment and occupational destination. The methodology applied consists of the specification and estimation of discrete choice models, and the empirical analysis is based on data provided by the Living Condition Survey (LCS) conducted for the Spanish National Statistics Institute (INE)
Keywords: Movilidad laboral; Human capital; Intergenerational ocupational mobility